Enhanced photocatalytic properties of ZnO/Al2O3 nanorod heterostructure. (13th April 2021) - Li, Zhipeng; Zhou, Ligong; Lu, Liying; Xu, Xiaoguang; Jiang, Yong
Abstract: The separation and transfer of the photoinduced charge carriers are essential for the high-efficient photocatalytic materials. Heterostructures which compose of several semiconductors can take advantage of energy level difference to improve photocatalytic properties. However, the fabrication of the related heterostructures normally adopts the physical vapor deposition method, such as atomic layer deposition, hindering the mass production of photocatalytic materials. In this work, ZnO nanorod arrays and ZnO/Al2 O3 heterostructure were prepared on Si (100) substrates by a cost-efficient method which combines the hydrothermal and photochemical techniques. Microstructure and surface composition analysis on the heterostructure confirm the synthesis of the ZnO/Al2 O3 core–shell heterostructure. According to the ultraviolet (UV)–visible diffuse reflectance spectroscopy, the band gap of the ZnO/Al2 O3 heterostructure can be estimated to be 3.25 eV, which is larger than that of pure ZnO nanorod arrays. Moreover, the heterostructure exhibits an obviously enhanced photocatalytic property for photodegradation of methyl orange under UV-irradiation. The energy band diagram of heterostructure shows that the improvement of photocatalytic property can be ascribed to the increase in the electron-hole pair separation rate. This work provides a simple method to fabricate nanoscale semiconductor heterostructures for photocatalytic applications.